Effect of disease-modifying drugs for spinal muscular atrophy on the ventilation support of type 1 children - Guo, W H (Zhonghua er ke za zhi = Chinese journal of pediatrics, 2024)
Objective: To summarize the effects of disease-modifying drugs for spinal muscular atrophy (SMA) on the ventilation support of type 1 children after acute respiratory failure. Methods: A case-control study was conducted, including the data of clinical characteristics, medication and ventilation supports of 38 SMA patients of type 1 with pneumonia and acute respiratory failure hospitalized in Children's Hospital Affiliated to Capital Institute of Pediatrics from January 2020 to July 2023. Children were divided into the treatment group and the untreated group based on whether they started and persisted in using Nusinersen or Risdiplam or not before hospitalization. The differences of ventilation support between the 2 groups were analyzed. The children of the treatment group were divided into the improved group and the unimproved group based on whether they could be avoid of prolonged dependence on continuous mechanical ventilation in the next six months after discharge. The differences in clinical characteristics between the two groups were analyzed. T-test and χ2 test were used for comparison. Results: Among the enrolled children, 19 were male and 19 were female. The age was 1.3 (0.6, 2.0) years at the time of hospitalization due to pneumonia. There were 26 cases in the treatment group and 12 cases in the untreated group. The treatment group had a higher proportion of patients without prolonged dependence on continuous mechanical ventilation in the next six months after discharge (69% (18/26) vs. 2/12, χ2=9.10, P<0.05). Eighteen children were improved among the treated group, while 8 children were not. The improved group had a larger age of first onset of acute respiratory failure (1.6 (0.4, 3.4) vs. 0.5 (0.3, 0.7) years, Z=2.07, P<0.05), a longer duration of medication taken before hospitalization (3.6 (2.4, 8.7) vs. 1.2 (1.2, 2.4) months, t=2.74, P<0.05), and a smaller proportion with underlying diseases (1/18 vs. 6/8, χ2=13.58, P<0.05). Conclusions: SMA disease-modifying drugs are useful for type 1 children to avoid of prolonged dependence on continuous mechanical ventilation after acute respiratory failure. The patients who take medication longer, or have acute respiratory failure for the first-time at an older age, or without underlying diseases are more likely to avoid of